Water Use Strategy of Reaumuria Songarica Population in Steppe Desert Region Based on Spatial Distribution - Wang Ru; Li Jinrong; Dong Lei; Zhang Zhijie; Luo Xiangying; Li Yingkun; Han Zhaoen (Shuitu baochi tongbao)
[Objective] The relationship between water adaptation and the distribution pattern of desert shrubs at the regional scale was studied and the process and mechanism of plant population response to environment in arid and semi-arid areas was analyzed in order to provide a basis for further understanding the co-evolution relationship between plants and environments. [Methods] The spatial distribution pattern and water use strategy of Reaumuria songarica populations were analyzed by using point pattern analysis and hydrogen and oxygen stable isotope tracing techniques. [Results] ① Under the complete spatial randomness model, the R. songarica population was uniformly distributed at <3 m scale, and aggregated at >32 m scale. The intra-population ecological relationship changed from competition to promotion. After habitat heterogeneity was eliminated, the population showed random distribution at > 30 m scale, and the intra-population ecological relationship showed a weakening trend, indicating that habitat heterogeneity played an important role in the formation of the spatial distribution pattern of the R. songarica population. This result indicated that habitat heterogeneity played an important role in the formation of the spatial distribution pattern of R. songarica populations at large scales. ② As the multi-year average precipitation decreased, the water use depth of the R. songarica population deepened from 0—20 cm to 60—100 cm. The density of the R. songarica population showed a highly significant negative correlation with multi-year precipitation (p<0.01). The change in vegetation cover at the sample site was mainly influenced by the herbaceous cover, and the change in R. songarica vegetation cover was not significant. [Conclusion] As multi-year average precipitation decreased, the distribution pattern of R. songarica populations was affected by environmental heterogeneity, and R. songarica adapted to environmental stress by increasing plant density and using deeper soil moisture.